The research question: the what, why and how in hand surgery - Farnebo, Simon; Harhaus-Wähner, Leila (The journal of hand surgery. European volume, 2024)
Identifying a good research question is one of the most important steps when laying the foundation of a research project. A good research question can aim to answer a hotly debated clinical issue, challenge a pre-existing dogma or make a contribution to specific aspects of a broader field of study. The difficulty in defining the question lies with pinpointing an important research topic or an area that is characterized by a lack of knowledge (the What), grasping the significance of how a precisely defined study can potentially impact on clinical practices (the Why) and determining the optimal study design tailored to answer the specific question (the How). These three domains constitute pivotal concepts in the process of shaping the research question.